Effects of simulated drought on biological soil quality, microbial diversity and yields under long-term conventional and organic agriculture. Issue 12 (5th October 2020) - Kundel, Dominika; Bodenhausen, Natacha; Jørgensen, Helene Bracht; Truu, Jaak; Birkhofer, Klaus; Hedlund, Katarina; Mäder, Paul; Fliessbach, Andreas
ABSTRACT: Drought and agricultural management influence soil microorganisms with unknown consequences for the functioning of agroecosystems. We simulated drought periods in organic (biodynamic) and conventional wheat fields and monitored effects on soil water content, microorganisms and crops. Above the wilting point, water content and microbial respiration were higher under biodynamic than conventional farming. Highest bacterial and fungal abundances were found in biodynamically managed soils, and distinct microbial communities characterised the farming systems. Most biological soil quality parameters and crop yields were only marginally affected by the experimental drought, except for arbuscular mycorrhizal fungi (AMF), which increased in abundance under the experimental drought in both farming systems. AMF were further strongly promoted by biodynamic farming resulting in almost three times higher AMF abundance under experimental drought in the biodynamic compared with the conventional farming system. Our data suggest an improved water storage capacity under biodynamic farming and confirms positive effects of biodynamic farming on biological soil quality. The interactive effects of the farming system and drought may further be investigated under more substantial droughts. Given the importance of AMF for the plant's water supply, more in-depth studies on AMF may help to clarify their role for yields under conditions predicted by future climate scenarios. Abstract : The impact of simulated summer drought on biological soil properties, microbial diversity and winter wheat yields was compared with rainout shelters under long-term conventional and organic agriculture.